2019
DOI: 10.1080/13102818.2019.1577699
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of silver nanoparticles using aqueous leaf extract of Premna integrifolia (L.) rich in polyphenols and evaluation of their antioxidant, antibacterial and cytotoxic activity

Abstract: View related articles View Crossmark data Citing articles: 7 View citing articles Green synthesis of silver nanoparticles using aqueous leaf extract of Premna integrifolia (L.) rich in polyphenols and evaluation of their antioxidant, antibacterial and cytotoxic activity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 37 publications
3
21
0
Order By: Relevance
“…Again, this supports the view that tiny size of nanoparticles may assist in easy penetration of microbial cell wall and destroy various organelles. Biosynthesized small NPs have been identified as being able to inhibit/destroy microbial cells (Singh et al 2019). In agreement with previous experimental results (Saranya and Gowrie 2016), this study suggested that the application of AgNPs synthesized from leaves and fruits aqueous extract of C. equisetifolia, could be used as an effective antimicrobial agent.…”
Section: Discussionsupporting
confidence: 91%
“…Again, this supports the view that tiny size of nanoparticles may assist in easy penetration of microbial cell wall and destroy various organelles. Biosynthesized small NPs have been identified as being able to inhibit/destroy microbial cells (Singh et al 2019). In agreement with previous experimental results (Saranya and Gowrie 2016), this study suggested that the application of AgNPs synthesized from leaves and fruits aqueous extract of C. equisetifolia, could be used as an effective antimicrobial agent.…”
Section: Discussionsupporting
confidence: 91%
“…In the low wavenumber region, they showed a shoulder at 1717 cm −1 which can be ascribed to the -COOH stretching of free carboxylic molecules, along with two strong bands, at 1640 cm −1 and 1387 cm −1 in the NPs from Leccino , and 1600 cm −1 and 1356 cm −1 in the NPs from Carolea . Such a double band can be accounted for by the signals of the antisymmetric and symmetric -COO- stretching of carboxylic molecules, respectively, coordinated to the surface Ag atoms [56,57] and thus responsible for the stabilization of the NPs in aqueous solution. Indeed, the same bands were observed also in the FTIR-ATR spectra of AgNPs, synthesized by the colloidal chemical route, by reduction of silver precursor in the presence of sodium citrate and tannic acid surfactants, which were coordinated to the AgNPs surface by their carboxyl groups.…”
Section: Resultsmentioning
confidence: 99%
“…Given the predominance of polyphenols like flavonoids and xanthones in fresh coconut inflorescence sap, it could be assumed that these compounds could be mainly involved in synthesis of NPs. Many studies have reported the role of polyphenols in the promotion of green synthesis of metal NPs (Tao et al, 2016;Jigaysa and Rajput, 2018;Singh et al, 2019;Latif et al, 2019).…”
Section: Metabolomic Profiling Of Coconut Inflorescence Sapmentioning
confidence: 99%